1984
DOI: 10.1063/1.447888
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence from the 1 1B u state of t r a n s,t r a n s-1,3,5,7-octatetraene in a free jet

Abstract: Freejet fluorescence excitation spectrum of t r a n s, t r a n s1,3,5,7octatetraene J. Chem. Phys. 75, 4338 (1981); 10.1063/1.442640Experimental confirmation of the dipole forbidden character of the lowest excited singlet state in 1,3,5,7 octatetraene J.The IIBu~1 lAg fluorescence spectrum of trans, trans 1,3,5,7-octatetraene in a supersonic helium jet has been determined. Excitation at the 1 IBu origin (35 549.3 cm -I) gives rise to a well resolved emission spectrum whose vibronic development is dominated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 12 publications
0
39
0
Order By: Relevance
“…Methyl groups are known to stabilize the S 2 (1 1 B u + ) states of polyenes. 28,29,4446,49,50 For example, measurements of the S 0 (1 1 A g – ) → S 2 (1 1 B u + ) transition energy of octatetraene (no terminal methyl groups) from supersonic jet studies give a (0–0) of 35 553 ± 5 cm –1 . 44,45,51 Decatetraene isolated in a supersonic jet has a S 0 → S 2 electronic origin of 34 783 ± 3 cm –1 , 28,29 giving a 770 cm –1 difference between the S 0 → S 2 transition energies of octatetraene and decatetraene.…”
Section: Resultsmentioning
confidence: 99%
“…Methyl groups are known to stabilize the S 2 (1 1 B u + ) states of polyenes. 28,29,4446,49,50 For example, measurements of the S 0 (1 1 A g – ) → S 2 (1 1 B u + ) transition energy of octatetraene (no terminal methyl groups) from supersonic jet studies give a (0–0) of 35 553 ± 5 cm –1 . 44,45,51 Decatetraene isolated in a supersonic jet has a S 0 → S 2 electronic origin of 34 783 ± 3 cm –1 , 28,29 giving a 770 cm –1 difference between the S 0 → S 2 transition energies of octatetraene and decatetraene.…”
Section: Resultsmentioning
confidence: 99%
“…22 Heimbrook et al measured the S 2 -S 0 emission in a supersonic expansion and estimated an S 2 lifetime of 100-300 ps. 27 Leopold et al reported a 18 cm -1 line width for the S 0 -S 2 (0-0) transition in the gas phase. 28 This gives a nonradiative lifetime of 300 fs.…”
Section: Introductionmentioning
confidence: 98%
“…For the first four systems ͑up to five double bonds͒, the experimental transition energies in gas phase are known. [11][12][13][14][15][16][17][18][19] Table IV reports the experimental as well as the calculated vertical transition energies. Figure 3 shows the shift in the transition energies with respect to butadiene.…”
Section: Polyenesmentioning
confidence: 99%